The Folded Land : A Relics Novel - Lebbon, Tim (London Titan Books, 2018)
Angela Gough has been pulled into this world, making her a criminal on the run. In London she encountered the Kin--satyrs and centaurs, Nephilim and wraiths, they are hunted and slaughtered for their body parts. Fleeing back to the United States, Angela discovers that the Kin are everywhere, and they are tired of being prey. When her niece Sammi is struck by lightning, she is drawn toward the mysterious Folded Land, and its powerful and deadly ruler. Helped by her lover Vince, caught in the midst of a Kin uprising, Angela must locate Sammi before the girl is lost forever
Keywords: Relics Novel -- Black market